2022
DOI: 10.1007/s00394-022-02851-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in the consumption of sugary and diet soft drinks among adolescents: a cross-national survey in 21 European countries

Abstract: To assess country-level trends in the prevalence of daily consumption of sugary (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) and diet (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) soft drinks among European adolescents, overall and by family material affluence. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Socio-economic status was successfully associated with fruit and vegetable consumption, as well as breakfast consumption frequency: students from more affluent families were more likely to report healthy food intake. These results seem to reflect the social inequalities’ patterns found in the literature, although no relation was found with ultra-processed foods [ 20 , 23 , 24 , 25 , 26 ]. Parents’ education level was positively associated with fruit and vegetable consumption and negatively associated with soft drink consumption, indicating a social inequality for students with lower-educated parents.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Socio-economic status was successfully associated with fruit and vegetable consumption, as well as breakfast consumption frequency: students from more affluent families were more likely to report healthy food intake. These results seem to reflect the social inequalities’ patterns found in the literature, although no relation was found with ultra-processed foods [ 20 , 23 , 24 , 25 , 26 ]. Parents’ education level was positively associated with fruit and vegetable consumption and negatively associated with soft drink consumption, indicating a social inequality for students with lower-educated parents.…”
Section: Discussionsupporting
confidence: 46%
“…Moreover, there is evidence that socio-economic status and parents’ educational level are relevant factors in predicting children’s overweight and obesity status, although they can have different and even opposite effects based on context (e.g., high-income countries vs. middle-income countries) [ 20 ]. Studies indicated that adolescents from low socio-economic status families show a higher prevalence of obesity and soft drink consumption [ 23 , 24 , 25 , 26 ]. Adolescents and children with lower-educated mothers were exposed to more fast-food outlets, although this did not affect Body Mass Index (BMI), according to a study from The Netherlands [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also makes it possible to look for their determinants within the individual and social realms of teenagers' lives, such as in the trend analysis of life satisfaction among European and North American adolescents completed by Cavallo et al [32]. Other HBSC data analyses presented trends in subjective complaints, physical activity, eating behaviours, and the occurrence of risk behaviours [33][34][35][36][37]. Analyses of changes in the quality of life, as measured by Cantril's ladder and the prevalence of repeated psychological complaints, are the most thematically consistent with this publication [32,38].…”
Section: Discussionmentioning
confidence: 99%
“…In this Perspective, we do not include sugar alcohols, which have about half the kilocalories of sugars. Sales and consumption of LCSs and LCS-containing beverages have increased globally since the 1990s [ [16] , [17] , [18] , [19] ], with some signs of a reduction in Europe [ 20 , 21 ]. In the United States, 48% of adults reported consuming at least one food or beverage containing LCSs in 2-d dietary assessments performed from 2007 to 2012 [ 22 ].…”
Section: Lcssmentioning
confidence: 99%